Cholesterol Inhibits M-type K(+) Channels via Protein Kinase C-dependent Phosphorylation in Sympathetic Neurons - Lee, Seul-Yi (American Society for Biochemistry and Molecular Biology, 2010)
M-type (KCNQ) potassium channels play an important role in regulating the action potential firing in neurons. Here, we investigated the effect of cholesterol on M current in superior cervical ganglion (SCG) sympathetic neurons, using the patch clamp technique. M current was inhibited in a dose-dependent manner by cholesterol loading with a methyl-β-cyclodextrin-cholesterol complex. This effect was prevented when membrane cholesterol level was restored by including empty methyl-β-cyclodextrin in the pipette solution. Dialysis of cells with AMP-PNP instead of ATP prevented cholesterol action on M currents. Protein kinase C (PKC) inhibitor, calphostin C, abolished cholesterol-induced inhibition whereas the PKC activator, PDBu, mimicked the inhibition of M currents by cholesterol. The in vitro kinase assay showed that KCNQ2 subunits of M channel can be phosphorylated by PKC. A KCNQ2 mutant that is defective in phosphorylation by PKC failed to show current inhibition not only by PDBu but also by cholesterol. These results indicate that cholesterol-induced inhibition of M currents is mediated by PKC phosphorylation. The inhibition of M currents by PDBu and cholesterol was completely blocked by PIP(2) loading, indicating that the decrease in PIP(2)-channel interaction underlies M channel inhibition by PKC-mediated phosphorylation. We conclude that cholesterol specifically regulates M currents in SCG neurons via PKC activation.